A preparation process of lightweight thermal insulation ceramic sand concrete material for exterior walls
By using silane coupling agent and hydrophobic agent in the ceramic sand to modify its surface, and adding dihydrogen phosphate and borax to the surface of the ceramic sand, combined with microcrack repair agent, the mechanical properties of the ceramic sand caused by water absorption in concrete are solved. The problem is reduced, improving the strength and waterproofing of concrete.
Patent Information
- Application Number
- CN202410875272.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-02
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-07-02
AI Technical Summary
The high water absorption of ceramic sand in concrete leads to a decrease in the mechanical properties of concrete, affecting construction fluidity and hydration reaction, and thus causing mechanical properties to decrease and shrinkage and cracking.
The ceramic sand is treated with silane coupling agent and hydrophobic agent to form a hydrophobic pore structure, and dihydrogen phosphate and borax are added to the surface of the ceramic sand to promote the hydration reaction with the concrete matrix, and combined with microcrack repair agent to improve strength and waterproofing performance. .
Effectively reduce the water absorption of ceramic sand, enhance its bonding force with concrete, improve the strength and waterproof performance of concrete, and prevent shrinkage cracks and degradation of thermal insulation performance.
Smart Images

Figure CN118666550B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal insulation concrete preparation, and in particular to a preparation process of a lightweight thermal insulation pottery sand concrete material for an exterior wall. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Lightweight thermal insulation concrete has the advantages of light weight, low thermal conductivity, thermal insulation and noise reduction, and can be used in building exterior wall insulation materials, roof panels, floor panels, partition boards, sound insulation boards, etc. Pottery sand is a kind of granular material with fine honeycomb microporous structure inside, which is fired at high temperature. It has the characteristics of low density, low thermal conductivity, good thermal insulation, fire resistance and frost resistance. Adding it to concrete can effectively improve its thermal insulation performance and reduce density.
[0004] However, due to the porous nature of ceramic sand, it will absorb a large amount of mixing water after being added to concrete materials. On the one hand, it will significantly reduce the fluidity of concrete, affecting construction. On the other hand, it will make it difficult for the hydration reaction of concrete materials to proceed fully, resulting in a decrease in mechanical properties and shrinkage and cracking in the later stage. If a large water-cement ratio is used, the porosity in the concrete will increase and the mechanical properties will decrease. Therefore, how to overcome the above problems caused by ceramic sand in concrete is crucial to the application of ceramic sand in concrete. Summary of the invention
[0005] The present invention provides a preparation process of an exterior wall lightweight thermal insulation ceramic sand concrete material, which effectively overcomes the problem that the high water absorption of ceramic sand leads to a decrease in the mechanical properties of the concrete material. Specifically, the technical solution of the present invention is as follows.
[0006] A preparation process of an exterior wall lightweight thermal insulation ceramic sand concrete material comprises the following steps:
[0007] (1) Add silane coupling agent and hydrophobic agent to anhydrous ethanol to form a dispersion, then add ceramic sand and heat and keep warm. After completion, separate the ceramic sand and dry it.
[0008] (2) applying a solution containing dihydrogen phosphate and borax to the dried pottery sand, mixing the mixture evenly and then drying the mixture to obtain pretreated pottery sand.
[0009] (3) Using silicate cement, the pretreated pottery sand, river sand fine aggregate, fly ash, fiber, dead-burned magnesium oxide, and micro-crack repairing agent as raw materials, mixing them evenly, adding mixing water, a water reducing agent, and a defoaming agent, and mixing them evenly to obtain a concrete material.
[0010] Furthermore, in step (1), the mass fraction of the silane coupling agent in the dispersion is 0.9-1.2%, and the amount of the hydrophobic agent added is 3-7 g / L.
[0011] Furthermore, in step (1), the silane coupling agent includes any one of kh550, kh560, kh570, etc.
[0012] Furthermore, in step (1), the hydrophobic agent includes: any one of tridecafluorooctyltriethoxysilane, perfluorodecyltriethoxysilane, polydimethylsiloxane, n-octyltriethoxysilane, etc.
[0013] Furthermore, in step (1), the solid-liquid ratio of the ceramic sand to the dispersion is 1 g: 25-45 ml. Optionally, the particle size of the ceramic sand is 1-5 mm.
[0014] Furthermore, in step (1), the heating temperature is 60-70° C., and the insulation time is 5-7 hours.
[0015] Furthermore, in step (1), the drying temperature is 75-80° C. and the drying time is 30-45 min.
[0016] Furthermore, in step (2), the solid-liquid ratio of the ceramic sand to the solution containing dihydrogen phosphate and borax is 1 g: 3-6 ml. Optionally, the dihydrogen phosphate in the solution is saturated, and the mass fraction of the borax is 10-15%.
[0017] Furthermore, in step (2), the dihydrogen phosphate includes at least one of potassium dihydrogen phosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, etc.
[0018] Furthermore, in step (2), the drying temperature is 60-70° C. and the drying time is 20-30 min.
[0019] Furthermore, in step (3), the silicate cement is 140-170 parts by weight, the pretreated pottery sand is 80-115 parts by weight, the river sand fine aggregate is 220-240 parts by weight, the fly ash is 60-71 parts, the fiber is 30-45 parts by weight, the dead-burned magnesium oxide is 12-18 parts by weight, and the micro-crack repair agent is 25-33 parts by weight.
[0020] Furthermore, in step (3), the fiber includes at least one of basalt fiber, polyethylene fiber, polypropylene fiber, polyacrylonitrile fiber, etc. Optionally, the length of the fiber is 1 to 3 cm.
[0021] Furthermore, in step (3), the amount of mixing water added is 50 to 70 parts by weight.
[0022] Furthermore, in step (3), the water reducer is added in an amount of 1.5-2.2% of the mass of silicate cement. Optionally, the water reducer includes any one of polycarboxylate water reducer, naphthalene water reducer, lignin sulfonate water reducer, etc.
[0023] Furthermore, in step (3), the defoamer dosage is 0.1-0.5% of the mass of silicate cement. Optionally, the defoamer includes any one of an organosilicon defoamer, a polyether defoamer, a mineral oil defoamer, etc.
[0024] Furthermore, in step (3), the microcrack repairing agent includes an inner core formed by mixing sulphoaluminate cement powder, calcium oxide powder and sodium stearate powder in a ratio of 4.5-7 parts by weight: 1.5-1.8 parts by weight: 0.6-0.72 parts by weight, and a paraffin coating layer coated on the surface of the inner core.
[0025] Furthermore, the microcrack repairing agent is prepared by the following method: the sulphoaluminate cement powder, calcium oxide powder and sodium stearate powder are mixed evenly in proportion, and then anhydrous ethanol-glycerol diluent is added to the obtained mixed powder, and the formed wet material is granulated after being stirred evenly. After completion, the obtained granules are dried, and then molten paraffin liquid is sprayed on the granules while rolling, and after mixing, the granules are thrown into anhydrous ethanol to cool, and after completion, the granules are separated, and the microcrack repairing agent is obtained after drying.
[0026] Furthermore, the ratio of the mixed powder to the diluent is 1 g: 0.15-0.22 ml. Optionally, the volume ratio of anhydrous ethanol to glycerol in the diluent is 1-1.5:1.
[0027] Furthermore, the drying temperature is 70-80° C. and the drying time is 20-30 min.
[0028] Furthermore, the ratio of the particulate matter to the molten paraffin liquid is 1 g: 0.4-0.6 ml. Optionally, the particle size of the particulate matter is 1-2 mm.
[0029] Compared with the prior art, the present invention has at least the following beneficial technical effects:
[0030] Concrete mixed with pottery sand is prone to cause a decrease in the mechanical properties of concrete due to the high water absorption of pottery sand. For this reason, the present invention first utilizes the high absorption characteristics of pottery sand to load a hydrophobic agent therein, and the internal pore structure of pottery sand is modified into hydrophobic pores, which can not only effectively reduce the water absorption of pottery sand, but also this method will not destroy the pore structure inside pottery sand, so that pottery sand maintains the characteristics of low thermal conductivity and light weight. Further, the present invention loads dihydrogen phosphate and borax on the surface and top layer of pottery sand, and after being mixed into concrete, the dihydrogen phosphate and dead-burned magnesium oxide are hydrated with the participation of mixing water to form a high-strength, high-bonding gelling hydration product, so that pottery sand is more firmly combined with the concrete matrix, and the bonding force between the matrix is insufficient due to the hydrophobicity of pottery sand, resulting in the problem of easy cracking at the interface of the two, and then causing the strength of the concrete material to decrease. At the same time, the above process of the present invention allows the reaction of the dihydrogen phosphate and the dead-burned magnesium oxide to be precisely controlled on the surface and surface of the pottery sand, which not only makes the pottery sand and the concrete matrix more firmly combined, but also reduces the reduction in thermal conductivity caused by the influence on the internal pore structure of the pottery sand. This is because the dihydrogen phosphate releases hydrogen ions after dissolving, so that an acidic environment is formed near the surface of the pottery sand, and then the dead-burned magnesium oxide here dissolves and releases magnesium ions, which further reacts with the dihydrogen phosphate metal hydration to form a gelled hydration product, while the dead-burned magnesium oxide in other parts of the concrete is in an alkaline environment formed by the hydration of silicate cement, so that it can remain stable and fill the pores in the concrete as a filler, which helps to improve the strength of the concrete. In addition, the pottery sand of the present invention constructs a water-repellent system for concrete, improving the waterproof ability of concrete materials.
[0031] In addition, the concrete material of the present invention is also mixed with a micro-crack repair agent with a paraffin coating layer formed by sulphoaluminate cement, calcium oxide and sodium stearate, which is convenient for repairing the micro-cracks generated in the concrete, and preventing the shrinkage cracks generated during the curing process from causing the thermal insulation performance of the concrete material of the present invention to decrease and water leakage. When micro-cracks occur in the concrete material, the repair agent at the cracks breaks due to the generation of cracks and exposes the various substances therein. After encountering water, the sulphoaluminate cement undergoes a hydration reaction to form an expansive gelled water product calcium aluminate, which can fill, bond and repair the cracks. At the same time, the calcium oxide not only releases calcium ions in the process of dissolving in water, but also generates heat, thereby facilitating the dissolution of the sodium stearate, and then reacting with the calcium ions to form a calcium stearate water repellent, which is doped in the hydration product of the sulphoaluminate cement to give it good water repellency, thereby improving the waterproof performance of the repaired cracks. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0033] Figure 1 This is a compressive strength test diagram of the specimen prepared in the following Example 1. DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0035] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meaning as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If not otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. Now, the technical solution of the present invention is further described in conjunction with specific embodiments.
[0036] Example 1
[0037] A preparation process of an exterior wall lightweight thermal insulation ceramic sand concrete material comprises the following steps:
[0038] (1) A silane coupling agent (kh570) and a hydrophobic agent (polydimethylsiloxane) were added to anhydrous ethanol and subjected to ultrasonic treatment for 20 minutes to form a dispersion, wherein the mass fraction of the silane coupling agent was 1.0% and the amount of the hydrophobic agent added was 3.5 g / L. Then, ceramic sand with a particle size distribution between 1 and 3 mm was added to the dispersion at a solid-liquid ratio of 1 g:40 ml, and the dispersion was heated to 70°C for 6 hours. After completion, the ceramic sand was separated by filtration, and then heated to 80°C for 30 minutes.
[0039] (2) Spraying a solution containing potassium dihydrogen phosphate and borax into the dried pottery sand at a solid-liquid ratio of 1 g:5 ml, wherein the potassium dihydrogen phosphate is in a saturated state and the mass fraction of the borax is 12%. After stirring and mixing evenly, heat to 65° C. and dry for 30 minutes to obtain pretreated pottery sand.
[0040] (3) Take 160 parts by weight of 42.5 silicate cement, 100 parts by weight of the pretreated pottery sand, 220 parts by weight of river sand fine aggregate with a particle size distribution between 0.5 and 1.5 mm, 71 parts by weight of fly ash, 38 parts by weight of polypropylene fiber with a length of 2 cm, and 15 parts by weight of dead-burned magnesium oxide powder. Mix the above raw materials and stir for 3 minutes, then add 66 parts by weight of mixing water, 3.2 parts by weight of polycarboxylic acid water reducer, and 0.48 parts by weight of organosilicon defoamer, and continue stirring for 2 minutes to obtain concrete material.
[0041] The concrete material prepared in this embodiment was poured into a mold, demoulded after forming, and naturally cured for 7 days. Then, the early compressive strength of the 150mm×150mm×150mm concrete specimen was obtained according to the "Concrete Physical and Mechanical Properties Test Method Standard" (GB / T 50081-2019). Figure 1 In addition, the contact angle of the test piece was tested, and the results were: compressive strength = 24.02 MPa, contact angle = 103.6°. It can be seen that the concrete material prepared in this embodiment exhibits hydrophobic properties (contact angle> 90°).
[0042] Example 2
[0043] A preparation process of an exterior wall lightweight thermal insulation ceramic sand concrete material comprises the following steps:
[0044] (1) A silane coupling agent (kh550) and a hydrophobic agent (perfluorodecyl triethoxysilane) were added to anhydrous ethanol and subjected to ultrasonic treatment for 20 minutes to form a dispersion, wherein the mass fraction of the silane coupling agent was 1.2% and the amount of the hydrophobic agent added was 7 g / L. Then, ceramic sand with a particle size distribution between 3 and 5 mm was added to the dispersion at a solid-liquid ratio of 1 g:25 ml, and the dispersion was heated to 70°C for 5 hours. After completion, the ceramic sand was separated by filtration, and then heated to 80°C for 40 minutes.
[0045] (2) Spraying a solution containing diammonium phosphate and borax into the dried pottery sand at a solid-liquid ratio of 1 g:6 ml, wherein the diammonium phosphate is in a saturated state and the mass fraction of borax is 10%. After stirring and mixing evenly, heat to 70° C. and dry for 20 minutes to obtain pretreated pottery sand.
[0046] (3) Take 140 parts by weight of 42.5 silicate cement, 80 parts by weight of the pretreated pottery sand, 233 parts by weight of river sand fine aggregate with a particle size distribution between 0.5 and 1.0 mm, 60 parts by weight of fly ash, 30 parts by weight of basalt fiber with a length of 3 cm, and 12 parts by weight of dead-burned magnesium oxide powder. Mix the above raw materials and stir for 3 minutes, then add 50 parts by weight of mixing water, 2.1 parts by weight of sodium lignin sulfonate water reducer, and 0.14 parts by weight of polyether defoamer, and continue stirring for 2 minutes to obtain concrete material.
[0047] The 7-day compressive strength and contact angle of the concrete material of this embodiment were tested by the same method as in Example 1. The results were: compressive strength = 22.18 MPa, contact angle = 110.9°, and it can be seen that the concrete material prepared in this embodiment exhibited hydrophobic properties (contact angle> 90°).
[0048] Example 3
[0049] A preparation process of an exterior wall lightweight thermal insulation ceramic sand concrete material comprises the following steps:
[0050] (1) A silane coupling agent (kh560) and a hydrophobic agent (tridecafluorooctyl triethoxysilane) were added to anhydrous ethanol and subjected to ultrasonic treatment for 25 minutes to form a dispersion, wherein the mass fraction of the silane coupling agent was 0.9% and the amount of the hydrophobic agent added was 7 g / L. Then, ceramic sand with a particle size distribution between 1 and 3 mm was added to the dispersion at a solid-liquid ratio of 1 g:45 ml, and the dispersion was heated to 60°C for 7 hours. After completion, the ceramic sand was separated by filtration, and then heated to 75°C for 45 minutes.
[0051] (2) Spraying a solution containing potassium dihydrogen phosphate and borax into the dried pottery sand at a solid-liquid ratio of 1 g:3 ml, wherein the potassium dihydrogen phosphate is in a saturated state and the mass fraction of the borax is 15%. After stirring and mixing evenly, heat to 60° C. and dry for 30 minutes to obtain pretreated pottery sand.
[0052] (3) Take 170 parts by weight of 42.5 silicate cement, 115 parts by weight of the pretreated pottery sand, 240 parts by weight of river sand fine aggregate with a particle size distribution between 0.5 and 1.0 mm, 67 parts by weight of fly ash, 45 parts by weight of polyethylene fiber with a length of 1 cm, and 18 parts by weight of dead-burned magnesium oxide powder. Mix the above raw materials and stir for 3 minutes, then add 70 parts by weight of mixing water, 3.74 parts by weight of polycarboxylate water reducer, and 0.85 parts by weight of polyether defoamer, and continue stirring for 2 minutes to obtain concrete material.
[0053] The 7-day compressive strength and contact angle of the concrete material of this embodiment were tested by the same method as in Example 1. The results were: compressive strength = 25.21 MPa, contact angle = 107.4°, and it can be seen that the concrete material prepared in this embodiment exhibited hydrophobic properties (contact angle> 90°).
[0054] Example 4
[0055] A preparation process of an exterior wall lightweight thermal insulation ceramic sand concrete material comprises the following steps:
[0056] (1) Sulphoaluminate cement powder, calcium oxide powder and sodium stearate powder are mixed in a ratio of 4.5 parts by weight: 1.5 parts by weight: 0.6 and stirred evenly. Then, anhydrous ethanol-glycerol diluent (wherein the volume ratio of anhydrous ethanol to glycerol is 1.5:1) is added to the obtained mixed powder in a ratio of 1g: 0.22ml, and the formed wet material is granulated after being stirred evenly. After completion, particles with a particle size of 1-2mm are screened out, dried at 80°C for 20min, and then melted paraffin liquid is sprayed on the particles while rolling (the ratio of particles to melted paraffin liquid is 1g: 0.4ml), and after rolling for 5min, the particles are thrown into anhydrous ethanol for cooling. After completion, the particles are separated and dried to obtain a microcrack repair agent.
[0057] (2) Take 162 parts by weight of 42.5 silicate cement, 110 parts by weight of the pretreated pottery sand prepared in Example 3, 230 parts by weight of river sand fine aggregate with a particle size distribution between 0.5 and 1.0 mm, 65 parts by weight of fly ash, 45 parts by weight of basalt fiber with a length of 3 cm, 18 parts by weight of dead-burned magnesium oxide powder, and 25 parts by weight of the microcrack repair agent of this example. Mix the above raw materials and stir for 3 minutes, then add 50 parts by weight of mixing water, 2.1 parts by weight of sodium lignin sulfonate water reducer, and 0.14 parts by weight of polyether defoamer, and continue stirring for 2 minutes to obtain concrete material.
[0058] The 7-day compressive strength and contact angle of the concrete material of this embodiment were tested by the same method as in Example 1. The results were: compressive strength = 27.07 MPa, contact angle = 122.4°, and it can be seen that the concrete material prepared in this embodiment exhibited good hydrophobic properties (contact angle> 90°).
[0059] Example 5
[0060] A preparation process of an exterior wall lightweight thermal insulation ceramic sand concrete material comprises the following steps:
[0061] (1) Sulphoaluminate cement powder, calcium oxide powder and sodium stearate powder are mixed in a ratio of 7 parts by weight: 1.8 parts by weight: 0.72 and stirred evenly. Then, anhydrous ethanol-glycerol diluent (wherein the volume ratio of anhydrous ethanol to glycerol is 1.0:1) is added to the obtained mixed powder in a ratio of 1g: 0.15ml, and the formed wet material is granulated after being stirred evenly. After completion, particles with a particle size of 1-2mm are screened out, dried at 70°C for 30min, and then melted paraffin liquid is sprayed on the particles while rolling (the ratio of particles to melted paraffin liquid is 1g: 0.6ml), and after rolling for 5min, the particles are thrown into anhydrous ethanol for cooling. After completion, the particles are separated and dried to obtain a microcrack repair agent.
[0062] (2) Take 156 parts by weight of 42.5 silicate cement, 91 parts by weight of the pretreated pottery sand prepared in Example 2, 235 parts by weight of river sand fine aggregate with a particle size distribution between 0.5 and 1.0 mm, 64 parts by weight of fly ash, 40 parts by weight of basalt fiber with a length of 3 cm, 18 parts by weight of dead-burned magnesium oxide powder, and 33 parts by weight of the microcrack repair agent of this example. Mix the above raw materials and stir for 3 minutes, then add 54 parts by weight of mixing water, 2.8 parts by weight of polycarboxylate water reducer, and 0.47 parts by weight of polyether defoamer, and continue stirring for 2 minutes to obtain concrete material.
[0063] The 7-day compressive strength and contact angle of the concrete material of this embodiment were tested by the same method as in Example 1. The results were: compressive strength = 26.44 MPa, contact angle = 118.6°, and it can be seen that the concrete material prepared in this embodiment exhibited good hydrophobic properties (contact angle> 90°).
[0064] Example 6
[0065] A preparation process of an exterior wall lightweight thermal insulation ceramic sand concrete material comprises the following steps:
[0066] (1) Take 160 parts by weight of 42.5 silicate cement, 100 parts by weight of pottery sand with a particle size distribution between 1 and 3 mm, 220 parts by weight of river sand fine aggregate with a particle size distribution between 0.5 and 1.5 mm, 71 parts by weight of fly ash, 38 parts by weight of polypropylene fiber with a length of 2 cm, and 15 parts by weight of dead-burned magnesium oxide powder.
[0067] (2) The raw materials in step (1) were mixed and stirred for 3 minutes, and then 66 parts by weight of mixing water, 3.2 parts by weight of polycarboxylic acid water-reducing agent, and 0.48 parts by weight of organosilicon defoaming agent were added and stirred for 2 minutes to obtain a concrete material.
[0068] The 7-day compressive strength and contact angle of the concrete material of this embodiment were tested by the same method as in Example 1. The results were: compressive strength = 13.46 MPa, contact angle = 51.7°, and it can be seen that the concrete material prepared in this embodiment exhibited obvious hydrophilic properties (contact angle < 90°).
[0069] Example 7
[0070] A preparation process of an exterior wall lightweight thermal insulation ceramic sand concrete material comprises the following steps:
[0071] (1) A silane coupling agent (kh560) and a hydrophobic agent (tridecafluorooctyl triethoxysilane) were added to anhydrous ethanol and subjected to ultrasonic treatment for 25 minutes to form a dispersion, wherein the mass fraction of the silane coupling agent was 0.9% and the amount of the hydrophobic agent added was 7 g / L. Then, ceramic sand with a particle size distribution between 1 and 3 mm was added to the dispersion at a solid-liquid ratio of 1 g:45 ml, and the dispersion was heated to 60°C for 7 hours. After completion, the ceramic sand was separated by filtration, and then heated to 75°C for 45 minutes.
[0072] (2) Spraying a solution containing potassium dihydrogen phosphate and borax into the dried pottery sand at a solid-liquid ratio of 1 g:3 ml, wherein the potassium dihydrogen phosphate is in a saturated state and the mass fraction of the borax is 15%. After stirring and mixing evenly, heat to 60° C. and dry for 30 minutes to obtain pretreated pottery sand.
[0073] (3) Take 170 parts by weight of 42.5 silicate cement, 115 parts by weight of the pretreated pottery sand, 240 parts by weight of river sand fine aggregate with a particle size distribution between 0.5 and 1.0 mm, 67 parts by weight of fly ash, and 45 parts by weight of polyethylene fiber with a length of 1 cm. Mix the above raw materials and stir for 3 minutes, then add 70 parts by weight of mixing water, 3.74 parts by weight of polycarboxylate water reducer, and 0.85 parts by weight of polyether defoamer, and continue stirring for 2 minutes to obtain concrete material.
[0074] The 7-day compressive strength and contact angle of the concrete material of this embodiment were tested by the same method as in Example 1. The results were: compressive strength = 21.14 MPa, contact angle = 105.1°, and it can be seen that the concrete material prepared in this embodiment exhibited hydrophobic properties (contact angle> 90°).
[0075] Example 8
[0076] A preparation process of an exterior wall lightweight thermal insulation ceramic sand concrete material comprises the following steps:
[0077] (1) A silane coupling agent (kh570) and a hydrophobic agent (polydimethylsiloxane) are added to anhydrous ethanol and ultrasonically treated for 20 minutes to form a dispersion, wherein the mass fraction of the silane coupling agent is 1.0%, and the amount of the hydrophobic agent added is 3.5 g / L. Then, ceramic sand with a particle size distribution between 1 and 3 mm is added to the dispersion at a solid-liquid ratio of 1g:40ml, and the dispersion is heated to 70°C for 6 hours. After completion, the ceramic sand is separated by filtration, and then heated to 80°C for 30 minutes to obtain pretreated ceramic sand.
[0078] (2) Take 160 parts by weight of 42.5 silicate cement, 100 parts by weight of the pretreated pottery sand, 220 parts by weight of river sand fine aggregate with a particle size distribution between 0.5 and 1.5 mm, 71 parts by weight of fly ash, 38 parts by weight of polypropylene fiber with a length of 2 cm, and 15 parts by weight of dead-burned magnesium oxide powder. Mix the above raw materials and stir for 3 minutes, then add 66 parts by weight of mixing water, 3.2 parts by weight of polycarboxylic acid water reducer, and 0.48 parts by weight of organosilicon defoamer, and continue stirring for 2 minutes to obtain concrete material.
[0079] The 7-day compressive strength and contact angle of the concrete material of this embodiment were tested by the same method as in Example 1. The results were: compressive strength = 20.07 MPa, contact angle = 99.8°, and it can be seen that the concrete material prepared in this embodiment exhibited hydrophobic properties (contact angle> 90°).
[0080] Example 9
[0081] A preparation process of an exterior wall lightweight thermal insulation ceramic sand concrete material comprises the following steps:
[0082] (1) Spray a solution containing diammonium phosphate and borax in pottery sand (with a particle size distribution between 3 and 5 mm) at a solid-liquid ratio of 1 g:6 ml, wherein the diammonium phosphate is in a saturated state and the mass fraction of borax is 10%. Stir and mix evenly, then heat to 70°C and dry for 20 minutes to obtain pretreated pottery sand.
[0083] (2) Take 140 parts by weight of 42.5 silicate cement, 80 parts by weight of the pretreated pottery sand, 233 parts by weight of river sand fine aggregate with a particle size distribution between 0.5 and 1.0 mm, 60 parts by weight of fly ash, 30 parts by weight of basalt fiber with a length of 3 cm, and 12 parts by weight of dead-burned magnesium oxide powder. Mix the above raw materials and stir for 3 minutes, then add 50 parts by weight of mixing water, 2.1 parts by weight of sodium lignin sulfonate water reducer, and 0.14 parts by weight of polyether defoamer, and continue stirring for 2 minutes to obtain concrete material.
[0084] The 7-day compressive strength and contact angle of the concrete material of this embodiment were tested by the same method as in Example 1. The results were: compressive strength = 14.85 MPa, contact angle = 56.3°, and it can be seen that the concrete material prepared in this embodiment exhibited obvious hydrophilic properties (contact angle < 90°).
[0085] Example 10
[0086] A preparation process of a lightweight thermal insulation ceramic sand concrete material for an exterior wall, which is different from the embodiment 1 in that the microcrack repair agent of this embodiment is prepared by the following method: sulphoaluminate cement powder, calcium nitrate powder and sodium stearate powder are mixed in a ratio of 4.5 parts by weight: 1.5 parts by weight: 0.6 and stirred evenly. Then, anhydrous ethanol-glycerol diluent (wherein the volume ratio of anhydrous ethanol to glycerol is 1.5: 1) is added to the obtained mixed powder in a ratio of 1g: 0.22ml, and the formed wet material is granulated after stirring evenly. After completion, granules with a particle size of 1-2mm are screened out, dried at 80°C for 20min, and then melted paraffin liquid is sprayed on the granules while rolling (the ratio of granules to melted paraffin liquid is 1g: 0.4ml), and the granules are thrown into anhydrous ethanol for cooling after rolling for 5min. After completion, the granules are separated and dried to obtain a microcrack repair agent.
[0087] The 7-day compressive strength and contact angle of the concrete material of this embodiment were tested by the same method as in Example 1. The results were: compressive strength = 26.89 MPa, contact angle = 113.2°, and it can be seen that the concrete material prepared in this embodiment exhibited good hydrophobic properties (contact angle> 90°).
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A preparation process of a lightweight thermal insulation ceramic sand concrete material for an exterior wall, characterized in that: The steps include: (1) Adding a silane coupling agent and a hydrophobic agent to anhydrous ethanol to form a dispersion, then adding ceramic sand and heating and keeping the dispersion, and after completion, separating the ceramic sand and drying it; (2) applying a solution containing dihydrogen phosphate and borax to the dried pottery sand, mixing them evenly and then drying them to obtain pretreated pottery sand; (3) using silicate cement, the pretreated pottery sand, river sand fine aggregate, fly ash, fiber, dead-burned magnesium oxide, and micro-crack repairing agent as raw materials, mixing them evenly, adding mixing water, a water reducing agent, and a defoaming agent, and mixing them evenly to obtain a concrete material; In step (2), the solid-liquid ratio of the ceramic sand to the solution containing dihydrogen phosphate and borax is 1 g: 3-6 ml, the dihydrogen phosphate in the solution is saturated, and the mass fraction of the borax is 10-15%; In step (3), the microcrack repairing agent includes an inner core formed by mixing sulphoaluminate cement powder, calcium oxide powder and sodium stearate powder in a ratio of 4.5-7 parts by weight: 1.5-1.8 parts by weight: 0.6-0.72 parts by weight, and a paraffin coating layer coated on the surface of the inner core.
2. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 1, characterized in that: In step (1), the mass fraction of the silane coupling agent in the dispersion is 0.9-1.2%, and the amount of the hydrophobic agent added is 3-7 g / L.
3. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 1, characterized in that: In step (1), the silane coupling agent includes any one of kh550, kh560, and kh570.
4. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 1, characterized in that: In step (1), the hydrophobic agent includes: any one of tridecafluorooctyltriethoxysilane, perfluorodecyltriethoxysilane, polydimethylsiloxane, and n-octyltriethoxysilane.
5. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 1, characterized in that: In step (1), the solid-to-liquid ratio of the ceramic sand to the dispersion is 1 g: 25-45 ml.
6. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 1, characterized in that: In step (1), the particle size of the ceramic sand is 1-5 mm.
7. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 1, characterized in that: In step (1), the heating temperature is 60-70° C. and the insulation time is 5-7 hours.
8. The preparation process of the lightweight thermal insulation ceramic sand concrete material for exterior walls according to claim 1, characterized in that: In step (1), the drying temperature is 75-80°C and the drying time is 30-45 minutes.
9. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 1, characterized in that: In step (2), the dihydrogen phosphate includes at least one of potassium dihydrogen phosphate, ammonium dihydrogen phosphate, and sodium dihydrogen phosphate.
10. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 1, characterized in that: In step (2), the drying temperature is 60-70° C. and the drying time is 20-30 min.
11. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 1, characterized in that: In step (3), the silicate cement is 140-170 parts by weight, the pretreated pottery sand is 80-115 parts by weight, the river sand fine aggregate is 220-240 parts by weight, the fly ash is 60-71 parts, the fiber is 30-45 parts by weight, the dead-burned magnesium oxide is 12-18 parts by weight, and the micro-crack repair agent is 25-33 parts by weight.
12. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 1, characterized in that: In step (3), the fiber includes at least one of basalt fiber, polyethylene fiber, polypropylene fiber, and polyacrylonitrile fiber.
13. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 1, characterized in that: The length of the fiber is 1 to 3 cm.
14. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 1, characterized in that: In step (3), the amount of mixing water added is 50 to 70 parts by weight.
15. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 1, characterized in that: In step (3), the water reducing agent is added in an amount of 1.5-2.2% of the mass of silicate cement.
16. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 1, characterized in that: In step (3), the water reducer includes any one of a polycarboxylate water reducer, a naphthalene-based water reducer, and a lignin sulfonate water reducer.
17. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 1, characterized in that: In step (3), the defoaming agent is added in an amount of 0.1-0.5% of the mass of silicate cement.
18. The process for preparing the lightweight thermal insulation ceramic sand concrete material for exterior walls according to claim 1, characterized in that: In step (3), the defoaming agent includes any one of a silicone defoaming agent, a polyether defoaming agent, and a mineral oil defoaming agent.
19. The process for preparing the lightweight thermal insulation ceramic sand concrete material for exterior walls according to any one of claims 1 to 18, characterized in that: The micro-crack repairing agent is prepared by the following method: the sulphoaluminate cement powder, calcium oxide powder and sodium stearate powder are mixed evenly in proportion, and then anhydrous ethanol-glycerol diluent is added to the obtained mixed powder, and the formed wet material is granulated after being stirred evenly; after completion, the obtained granules are dried, and then molten paraffin liquid is sprayed on the granules while rolling, and after mixing, the granules are thrown into anhydrous ethanol to cool, and after completion, the granules are separated, and the micro-crack repairing agent is obtained after drying.
20. The process for preparing the lightweight thermal insulation ceramic sand concrete material for exterior walls according to claim 19, characterized in that: The ratio of the mixed powder to the diluent is 1g:0.15-0.22ml.
21. The process for preparing the lightweight thermal insulation ceramic sand concrete material for exterior walls according to claim 20, characterized in that: The volume ratio of anhydrous ethanol to glycerol in the diluent is 1-1.5:
1.
22. The process for preparing the lightweight thermal insulation ceramic sand concrete material for exterior walls according to claim 20, characterized in that: The drying temperature is 70-80°C and the drying time is 20-30 minutes.
23. The preparation process of the exterior wall lightweight thermal insulation ceramic sand concrete material according to claim 20, characterized in that: The ratio of the particles to the molten paraffin liquid is 1g:0.4-0.6ml.
24. The process for preparing the lightweight thermal insulation ceramic sand concrete material for exterior walls according to claim 20, characterized in that: The particle size of the particles is 1-2 mm.
Citation Information
Patent Citations
Fabricated thermal-insulation wallboard material capable of realizing rapid demoulding and preparation method of fabricated thermal-insulation wallboard material
CN108610089A
Preparation process of underground tunnel light lane plate based on UHPC (Ultra High Performance Concrete)
CN117700187A
